Rapid Antiretroviral Therapy Initiation following roll out of Point-of-Care Early Infant Diagnosis Testing, Uganda, 2018- 2021 - Migamba, Stella M.; Nsubuga, Edirisa Juniour; Kwiringira, Andrew; Kabwama, Steven N.; Nakafeero, Mary; Bulage, Lilian; Ario, Alex R. (AIDS Res Ther, 2024)
Uganda Ministry of Health recommends a first HIV DNA-PCR test at 4-6 weeks for early infant diagnosis (EID) of HIV-exposed infants (HEIs), immediate results return and initiation of antiretroviral therapy (ART) for HIV-positive infants. In 2019, MOH introduced point-of-care (POC) whole-blood EID testing in 33 health facilities and scaled up to 133 in 2020. We assessed turnaround time for test results and ART linkage before and after implementation of POC testing.